2019
DOI: 10.1108/itp-05-2018-0255
|View full text |Cite
|
Sign up to set email alerts
|

Preventing identity theft

Abstract: This document may differ from the final, published version of the research and has been made available online in accordance with publisher policies. To read and/or cite from the published version of the research, please visit the publisher's website (a subscription may be required.)Preventing identity theft: identifying major barriers to knowledge-sharing in online retail organisations Abstract Purpose -Knowledge-sharing (KS) for preventing identity theft has become a major challenge for organisations. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 114 publications
(141 reference statements)
1
14
0
Order By: Relevance
“…Moreover, Yih-Tong et al [6] also point to at this level, the fear about the knowledge being inadequate or unimpressive. Maitlo et al [37] found in their study that the lack of opportunity for employees to learn about CK was one of the major barriers. In addition, job rotation is vital for the enhancing the knowledge of individuals [103] specially in jobs that involve dealing with changing conditions in a turbulent environment [37].…”
Section: Means/humanmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, Yih-Tong et al [6] also point to at this level, the fear about the knowledge being inadequate or unimpressive. Maitlo et al [37] found in their study that the lack of opportunity for employees to learn about CK was one of the major barriers. In addition, job rotation is vital for the enhancing the knowledge of individuals [103] specially in jobs that involve dealing with changing conditions in a turbulent environment [37].…”
Section: Means/humanmentioning
confidence: 99%
“…Trust [29,37] Fear, disbelief, apprehension, scepticism, copy and imitation, inflexibility and complexity Therefore, the main purpose of the present paper is to identify and frame the most significant barriers in the process of CKM in networked enterprises by using three aspects (i) perspectives in the CKM process; (ii) levels of CKM, including extra-CK level as an innovative concept, and (iii) barrier blocks that obstruct the CKM process.…”
Section: Block Thematic Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations